Stress, nutrients and genotype: understanding and managing asparagine accumulation in wheat grain - Joseph Oddy; Sarah Raffan; Mark D. Wilkinson; J. Stephen Elmore; Nigel G. Halford (CABI Agriculture and Bioscience)
Abstract Plant stress and poor crop management strategies compromise the foundations of food security: crop yield, nutritional quality and food safety. Accumulation of high concentrations of the amino acid asparagine in its free (soluble, non-protein) form is an example of an undesirable outcome of stress for the nutritional quality and food safety of wheat because of its role as a precursor to acrylamide, a carcinogenic processing contaminant. In this review, we cover what is known about the mechanisms and functions of free asparagine accumulation in the grain during normal development and particularly during stress in wheat. Comparisons with other plant species, yeast, and mammals are drawn in order to gain deeper insight into the conserved biology underlying asparagine accumulation. Crop management strategies and practices are discussed in the context of managing asparagine accumulation, which must be balanced against other desirable goals, such as sustainability, protein content and yield.